Design and Implementation of Economics Teaching Module Based on Discovery Learning, Its Effect on Students' Critical Thinking Ability - Dewi Ayu Sakdiyyah; Wahjoedi; Lisa Rokhmani (CV. AFDIFAL MAJU BERKAH, 2022)
In 2021, the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia will begin to promote an independent curriculum. This curriculum was developed to support the recovery of learning due to the COVID-19 pandemic. On the other hand, students in the 21st century also need to be empowered with critical thinking skills. So that relevant learning tools are needed to improve students' critical thinking skills. This study aims to produce an economics learning module based on discovery learning in an independent curriculum to improve students' critical thinking skills. The method used in this research is Research and Development (R&D) using the Borg & Gall model. The instruments used in this study were expert validation sheets and critical thinking skills tests given to students in class X6 and X7 at the State Senior High School 5 Taruna Brawijaya, Kediri City. Based on the results of the validation of module experts and material experts on the products developed, the average value of 91.5% indicates that the discovery learning-based economics teaching module is very feasible to be used in the learning process. Meanwhile, based on the results of the independent sample t-test in the Equal variances section, it is assumed that the sig value is known. (2-tailed) of 0.000<0.05. So it can be said that there is a significant difference between the average student learning outcomes in the post-test experimental class and post-test control class. Based on the output descriptive statistics table, it is also known that the average score for the experimental class post-test is 89.50, while the control class post-test is 85.30. So it can be said that this product is effectively used in learning based on the results of the post-test in the experimental class which shows a higher score than the control class. Therefore, it is recommended that the class X economics teacher use this teaching module as an alternative support in the learning process.